Pengaruh Discount Policy Terhadap Tingkat Penjualan - Imbrani, Hari (Rifa'Institute, 2021)
The discount policy applied by the company will affect the level of sales, how the company applies the discount policy and how the sales level increases due to the policy and how much influence the implementation of this discount policy has on the company's sales level. This type of research is descriptive statistics with a correlational approach. The study concludes that discount policy has an effect on increasing sales at PT. Lembang Abadi Indah Bandung by 93%, the remaining 7% is influenced by factors, the magnitude of the significant influence is with a very strong relationship between the two variables, namely 0.965, the relationship is functionally with a linear regression approach, namely Y = 1.650. 267 + 13,687X, the results of the hypothesis test state that Ho is rejected and Ha is accepted because t count (10.335) > t table (4.473).